Aging time influences fatty acid profiles and volatile compounds in cooked Thai native beef. - Meenongyai, Watcharawit; Kaewka, Kunwadee; Wongpanit, Kannika; Phongkaew, Piyamas; Khejornsart, Pichad; Khumpeerawat, Panuwat; Stelzleni, Alexander Michael (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aims to assess the impact of aging time on the quality of meat, fatty acid profiles, and volatile compounds in cooked Thai native beef. Materials and Methods: The experiment utilized a randomized complete block design, where the aging time (0, 7, 14, 21, and 28 days) served as the treatment and the longissimus thoracis et lumborum muscle from Thai native cattle (n = 4) was considered a block. Results: Meat color and Warner-Bratzler shear force values decreased as the aging time increased. Furthermore, the moisture content decreased while the protein and ash content increased with a longer aging time. The proportions of fatty acids showed significant differences with varying aging times. These fatty acids exhibited the highest proportions in the 14-day dry-aged beef samples. The levels of short-chain aldehydes (pentanal, heptanal, octanal, nonanal, decanal, and 2-nonenal) and alcohols (1-hexanol and 1-octanol) decreased as the aging time increased. However, there was an increase in long-chain aldehydes (tetradecanal, hexadecanal, heptadecanal, and octadecanal) with longer aging time. In addition, the levels of toluene, dodecane, tridecane, methyl-pyrazine, 2,5-dimethyl-pyrazine, trimethyl-pyrazine, and dimethyl trisulfide were higher in 14-day dry-aged beef compared to beef that had not been aged. Furthermore, a correlation was found between the number of the 6 significant fatty acids in the dry-aged beef samples and the 12 volatile compounds in cooked beef. Conclusion: Our results suggest that aging times significantly influence the fatty acid profiles of Thai native beef, which in turn are correlated with the characteristic volatile compounds. J. Adv. Vet. Anim. Res., 12(1): 179–191, March 2025 http://doi.org/10.5455/javar.2025.l885